Monitoring System of Hydroponic Using Solar Energy - Kamarulzaman, Muhammad Syahmi; Jumaat, Siti Amely; Ismail, Muhammad Nafis; Mohd Nor, Ahmad Fateh (Journal of Electronic Voltage and Application, 2021)
This project aims to a solar-powered hydroponic monitoring system. The hydroponic system is a plantation system that uses water as the medium instead of soil. Solar energy is the main source and as a supply the Arduino Uno, a microcontroller to control all the sensors then collecting the data and display the data to users. The sensors that were used were DS18B20 temperature sensor, propylene float water level sensor and pH sensor. This sensor will monitor those elements and help the users in the hydroponics system. An Arduino Ide software used to develop coding for the monitoring system. The value of temperature, water level and pH had been measured and collected to be analyzed. In conclusion, this project is successful as the data collected was satisfied with the objective and the result shows the effectiveness of a solar-powered hydroponic monitoring system.Keywords: Hydroponic, Solar, Arduino